ABHÄNGEN - Ein- und Ausgrenzen, Kanonisieren, Kollaborieren in Pop, Kunst und Medien. - Jacke, Christoph (Impulse. Texte und Bilder zur Kunstvermittlung.)

Editorial. - Jacke, Christoph; Autsch, Sabine; Pickartz, Tim (Impulse. Texte und Bilder zur Kunstvermittlung.)

On the Integration of Sampling Rate Synchronization and Acoustic Beamforming - Gburrek, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))

Nietzsche’s Search for Philosophy: On the Middle Writings Keith Ansell-Pearson - Corall, Niklas (The Agonist)
In Nietzsche’s Search for Philosophy – On the Middle Writings, Keith Ansell Pearson directs his interpretive gaze to the middle writings of Nietzsche’s oeuvre, namely Human, All Too Human (HAH), Dawn and The Gay Science (GS). While at least in German Nietzsche scholarship, it is rather debatable whether or not the middle writings should have been considered “neglected”– with perhaps Dawn being a reasonable exception – it is important to read them as more than merely a detour from the “real Nietzsche” found in the Birth of Tragedy and then the late works. While Ansell-Pearson does not presume a homogeneous philosophical approach in the middle works, he characterizes the period as a whole and each work in itself as containing important aspects of Nietzsche’s “search for philosophy”, especially in consideration of Nietzsche’s attempts to “unify thought and life” (4) in what is labelled a “‘philosophical life’” (4).
Keywords: Ocean Engineering

Digitale Bruchstücke zwischen Faktalismus und Zukunftsnarration: Der Letzte Mensch und Algorithmische Regime - Corall, Niklas (Nietzsche, die Medien und die Künste im Zeitalter der Digitalisierung)

Digitizing Processes in Manufacturing Companies via Low-Code Software (to appear) - Weidmann, Nils; Kirchhoff, Jonas; Sauer, Stefan
Low-code development platforms (LCDPs) recently sparked interest in both academia and industry, promising to speed up software development and make it accessible to users with little or no programming experience. Thus, the mass-development of software applications that are custom-made to the tasks, skills, and preferences of end users is potentially enabled. Although different LCDPs have been analysed with respect to their functionality and applied to exemplary case studies in recent work, there is a shortage of experience reports in which LCDPs are used to digitize business processes in small and medium manufacturing enterprises. In this paper, we therefore summarize our experience from supporting industry partners to identify business processes that are suitable for being implemented with low-code technologies and to select an LCDP that meets the requirements of the business process while aligning with the overall digitization strategy of the respective company. We also present the opportunities and challenges of the low-code approach as perceived by industry partners. In summary, the low-code approach should be seen as an essential factor for the digitization of business processes in small and medium manufacturing companies.

Creativity in entrepreneurship: Dancing between nothing and structure - Hubner-Benz, Sylvia; Frese, Michael (Handbook of Organizational Creativity)

Tod mit Kindern thematisieren - Magdeburg, Lena Maria (Grundschule)

Medienpädagogische Professionalisierung in der beruflichen Weiterbildung. Eine Studie aus Perspektive der biografischen Medienforschung - Dehmel, Lukas

Novel Cascaded Incremental Nonlinear Dynamic Inversion Controller Approach for a Tiltrotor VTOL - Henkenjohann, Mark; Nolte, Udo; Henke, Christian; Trächtler, Ansgar (2023 International Conference on Unmanned Aircraft Systems (ICUAS))

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.

Softsensor model of phase transformation during flow forming of metastable austenitic steel AISI 304L - Rozo Vasquez, Julian; Arian, Bahman; Kersting, Lukas; Walther, Frank; Homberg, Werner; Trächtler, Ansgar

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Aachen 2022)

Case Study III: Challenges of lightweight design, vehicles, and rescuers - Akbulut Irmak, Emine Fulya; Hanses, Hendrik; Horwath, Ilona; Tröster, Thomas (Climate Protection, Resource Efficiency, and Sustainable Engineering)

Introduction to the Minitrack on Data-driven Services in Manufacturing: Innovation, Engineering, Transformation, and Management - Koldewey, Christian; Martin, Rabe; Dumitrescu, Roman; Winter, Johannes (Proceedings of the 56th Hawaii International Conference on System Sciences)

Evaluation of the effects of different heating strategies on the joining partners during infrared welding of black polyamides - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J.

Evaluation of Infrared Welded Joints of Short Fiber Reinforced Thermoplastics Using Digital Image Correlation - Schöppner, Volker; Gevers, Karina; Schraa, L.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Proceedings of the 2023 International Conference on Composite Materials)

Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen (QSS) von Thermoplasten - Schöppner, Volker; Arndt, Theresa (Joining Plastics)

Dielectric Heating in the Vulcanization Process of Rubber Extrudates - Schöppner, Volker; Petzke, J.

Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian